2021
DOI: 10.3390/jcm11010102
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Beta-Thalassemia: Systematic Review

Abstract: In the last half century, the life expectancy of beta-thalassemia patients has strikingly increased mostly due to regular blood transfusions and chelation treatments. The improved survival, however, has allowed for the emergence of comorbidities, such as hearing loss, with a non-negligible impact on the patients’ quality of life. This thorough review analyzes the acquired knowledge regarding hearing impairment in this hereditary hemoglobinopathy, aiming at defining its prevalence, features, course, and possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 54 publications
(119 reference statements)
2
21
0
Order By: Relevance
“…This complication has not been found to be related to age, sex, and ferritin level in many studies. However, Tartaglione's study reported a weak correlation between hearing loss, clinical phenotype, and iron chelator 37 …”
Section: Discussionmentioning
confidence: 97%
“…This complication has not been found to be related to age, sex, and ferritin level in many studies. However, Tartaglione's study reported a weak correlation between hearing loss, clinical phenotype, and iron chelator 37 …”
Section: Discussionmentioning
confidence: 97%
“…">Diagnosis of hearing loss was made after audiometry had been conducted. Excluding patients who had a diagnosis of anemia (ICD‐9‐CM 280‐285) and/or nutritional deficiencies (ICD‐9‐CM 260‐269) because these diagnoses may also affect the risk of hearing loss 33,34 …”
Section: Methodsmentioning
confidence: 99%
“…Despite high prevalence of deferasirox consumption and numerous studies accessible in the literature, the true scenarios of visual and auditory complications in beta-thalassemia remain fairly inaccurate. In addition, the findings are markedly heterogeneous and inconsistent, with prevalence rates ranging from no visual and auditory disorders to visual and hearing impairment in patients (6,(8)(9)(10). The present study aimed to monitor visual complications such as color blindness, visual acuity change, cataracts, glaucoma, and retinal disorders, as well as auditory complications such as sensorineural hearing loss, tinnitus, and deafness which are the results of deferasirox consumption.…”
Section: Introductionmentioning
confidence: 98%
“…Several case reports reported an association between the onset of chelation therapy and occurrence of ocular symptoms (7)(8)(9). Also, auditory disorders occur during treatment with these agents for an extended period at high doses and in patients with augmented ferritin levels (7,10,11). Over the last few decades, there have been dramatic developments in survival for patients with thalassemia major due in large measure to enhanced iron chelators.…”
Section: Introductionmentioning
confidence: 99%